2020
DOI: 10.1519/jsc.0000000000003866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydration Educational Intervention in High School Football Players

Abstract: Atkins, WC, McDermott, BP, Kanemura, K, Adams, JD, and Kavouras, S. Effects of Hydration Educational Intervention in High School Football Players. J Strength Cond Res 35(2): 385–390, 2021—The purpose of this study was to assess the effects of a one-time educational intervention (EI) on hydration behaviors, status, and knowledge. In a pre-test, post-test quasi-experimental design, 41 in-season American high school football players (16 ± 1 years) voluntarily participated. Teams were assigned to EI or no interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Three studies did not report the specific sports played by the study population. Eighteen studies recruited participants from one type of sport including swimming ( 9 , 22 , 31 , 49 ) , basketball ( 28 , 30 , 44 ) , soccer ( 41 , 43 ) , gymnastics ( 21 ) , ballet ( 20 ) , rugby ( 57 ) , table tennis ( 23 ) , American football ( 24 ) , cross-country skiing ( 38 ) , handball ( 37 ) , volleyball ( 29 ) and synchronised swimming ( 40 ) . The remaining studies represented various sports, including track and field ( 47 ) , aesthetic sports ( 39 ) , endurance sports ( 34 , 35 ) and various team and individual sports ( 25 27 , 36 , 42 , 45 , 46 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not report the specific sports played by the study population. Eighteen studies recruited participants from one type of sport including swimming ( 9 , 22 , 31 , 49 ) , basketball ( 28 , 30 , 44 ) , soccer ( 41 , 43 ) , gymnastics ( 21 ) , ballet ( 20 ) , rugby ( 57 ) , table tennis ( 23 ) , American football ( 24 ) , cross-country skiing ( 38 ) , handball ( 37 ) , volleyball ( 29 ) and synchronised swimming ( 40 ) . The remaining studies represented various sports, including track and field ( 47 ) , aesthetic sports ( 39 ) , endurance sports ( 34 , 35 ) and various team and individual sports ( 25 27 , 36 , 42 , 45 , 46 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies represented various sports, including track and field (47) , aesthetic sports (39) , endurance sports (34,35) and various team and individual sports (25)(26)(27)36,42,45,46) . Sporting levels included competitive (9,(21)(22)(23)26,30,32,34,35,39,40,42,49) , regional/state/national competitors (27)(28)(29)(36)(37)(38)43,47) , high school/college (19,24,27,33,41,45,57) , elite (20,44,46) and one study did not report sporting level (25) . NK was assessed using twenty-one questionnaires across thirty-two studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Rehydration post-exercise is going to be dependent on the duration and type of exercise, dietary needs of the athlete, and individual sweat rate. Hydration education on post-exercise rehydration is also necessary to ensure fluids are adequately replaced prior to the next exercise bout (Maughan et al, 1997 ; Armstrong et al, 1998 ; Maughan and Shirreffs, 2010b ; Park et al, 2012 ; Atkins et al, 2021 ). Current guidelines suggest either replacing fluids to match sweat losses or replacing 150% of fluid losses when there is a short recovery period (i.e., 4 h) (Shirreffs et al, 2007 ; McDermott et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that educational intervention on hydration improves hydration status and enhances exercise performance in athletic youth [ 47 ]. Atkins WC et al [ 48 ] have reported that educational intervention improves hydration status and behaviours in high school football players. Martín-Payo [ 49 ] has also reported that feasible educational intervention improves hydration behaviour in adolescent soccer players, but hydration guidelines should be based on personal factors.…”
Section: Discussionmentioning
confidence: 99%